Using Cultural Historical Activity Theory (CHAT) as a Framework to Understand Children's Play with Digital Technologies. In: paper presented at 1st Malaysia International Counselling Conference " Best Practices for Best Practitioners in Counselling Services:29-31 October 2014, Hilton Hotel , Kuching Sarawak. - Shaziti, Aman; Amalia, Madihie (2014)
This paper aims to introduce Engeström’s CHAT to ccounsellors working with minor clients addicted to digital technologies. The paper adiscusses the application of CHAT as a framework to understand the cultural and historical factors involved in an to inform the current dialogue on children’s ‘addiction’ to gadgets as tools for play. CHAT is able to clarify the root of ‘cognition and emotional disturbances’ in the thinking system of children’s addiction behaviour. Blame seems to fall solely on these digital tools without examining the social or environmental factors such as parental roles. Children’s predisposition to digital play could only be fully understood by looking at the wider context of the play activity; the children’s motives and goals, the tools used, the actions and interactions with the technologies, the larger community in which the play occurs, and the rules and norms informing what the children do and how they play. Exploring these facets may uncover the origins of children’s play with technology and the development of ‘addiction’ to such technologies. This understanding can be used to inform the best way forward in today’s world that have digital technologies permeating children’s everyday lives. Recommendations are presented for child counsellors in order to work with children (minor client) in understanding and intervening the addiction to digital technologies.